The missing text - Lewandowska, Marysia; Buck, Paul; Foale, Susan; McCann, Graham; McGeown, Martin; Probyn, Elspeth; Reason, David; Wear, Eric (London : Chance Books London, 1991)
Would it be possible at this time to strategically implicate unwelcome and disruptive histories into the centre, so that they may in their turn question what constitutes and maintains the identity of the centre, and to test what would render it marginal. This volume presents itself as a timely disruption. Not a generalized disorder, but a specific contestation of the habitual oppositions of text and image, theory and practice where the assumptions implicit in their hierarchical distribution are thrown off balance. We are at a point where theory could be seen to have reduced art to a footnote, a supplement which fulfills the conditions required of it by the overdeterminations of a dominant discourse. A function of the texts collected here is not to fix the visual but to invite the slide.
Engels
boek
Keywords: Williams, John; Kovats, Tania; Dronsfield, Jonathan; Mahr, Mari; Gordon, Douglas; Douglas, Stan; Surprenant, Céline; Speller, Stephen